CHI3L1 alleviate acute liver injury by inhibiting Th1 cells differentiation through STAT3 signaling pathway - Zhang, Shaopeng (Ann Transl Med, 2021)
BACKGROUND: Acute liver injury (ALI) is a severe liver disease. Chitinase 3-like-1 (CHI3L1), a protein belonging to the glycosyl hydrolase family 18, is involved in many diseases, such as inflammatory diseases, bacterial infections, and various malignant tumors; however, the function of CHI3L1 in ALI remains unclear. The objective of this study was to evaluate the protective functions of CHI3L1 against thioacetamide (TAA)-induced ALI in mice and explore its potential mechanisms. METHODS: Data from 20 patients with ALI and 10 healthy subjects was collected. Serum CHI3L1, serum aspartate transaminase (AST), and serum alanine aminotransferase (ALT) were measured. To establish ALI mouse models, thioacetamide was intraperitoneally injected into groups of the CHI3L1-knockout (CHI3L1-KO) and wild-type (WT) mice (80 and 150 mg/kg). Recombinant CHI3L1 protein (rCHI3L1) (5 µg/kg), IFN-γ (500 ng), and WP1033 (an inhibitor of P-STAT3, 0.2 mL) were injected before TAA treatment, after which the effects were estimated. Splenic CD4+CD62L+ naive T cells were isolated from CHI3L1-KO mice and stimulated to differentiate into regulatory T (Treg) cells, T-helper 1 (Th1) cells, T-helper 2 (Th2) cells, and T-helper 17 (Th17) cells. RESULTS: Increased serum CHI3L1 levels were seen both in healthy subjects and post-therapy patients compared with ALI patients. CHI3L1 levels were negatively correlated with serum ALT and AST levels in ALI patients. CHI3L1-KO group showed higher serum ALT and AST levels than the WT group following TAA treatment, while tail vein injection of rCHI3L1 reduced liver tissue injury and improved Treg cell differentiation in vivo. In vitro experiment showed that knockout of CHI3L1 improved IFN-γ+ Th1 cell differentiation. Furthermore, intraperitoneal administration of IFN-γ produced more severe hepatocellular necrosis compared with rCHI3L1 injection alone. Mechanism study showed that T-box expressed in T cells (T-bet), and signal transducer and activator of transcription 3 (STAT3), play a critical role in adversely mediating the effect of CHI3L1, which is consistent with the finding that treatment with WP1033 down-regulated the differentiation of the Th1 cells in vitro and reduced severity of liver injury in vivo. CONCLUSIONS: CHI3L1 reduced the production of IFN-γ and inhibited Th1 cell differentiation through the STAT3 signaling pathway, which could be a potential therapeutic strategy for treating ALI.